Rice Bran Oil Extraction: A valuable First Step Towards Edible Oil - Naulina, Rosada Yulianti; Novitasari, Diana; Irmawati, Devi; Zullaikah, Siti (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
Rice bran has the potential to become a nutritional component that reduces disease risk and improves physical health. In addition, rice bran is a hypoallergenic (allergen-free) component which is a good source of dietary fiber. Rice bran oil extraction (RBO) is one of the most popular uses of rice bran. Judging from the health benefits and healthier composition, rice bran oil is very appropriate. The most unsaturated fatty acids are found in rice bran oil which has a composition of 80% unsaturated fatty acids. In taking yields, the extraction method is a practical and effective technique. This research aims to understand the effect of temperature, mesh size, and extraction time on the yield value and FFA RBO content. This Soxhlet uses several variables, with temperature variables of 60°C, 65°C, 70°C, 75°C, 80°C while time variables of 1, 2, 3, 4, and 5 hours with variations in mesh size of 100 and 60. The research results show that soxhletation extraction at mesh 100 optimum increases at a temperature of 70°C within 4 hours. Where the yield of oil produced was 11.62%. Meanwhile, for mesh 60, the optimum increase occurred at a temperature of 65°C within 4 hours with an oil yield of 12.90%. Rice bran oil extraction, the content of in rice bran oil extraction, the content of alkenes, aldehydes, and alkene bending.